Outcomes of Adolescent and Adult Patients with Lung Metastatic Osteosarcoma and Comparison of Synchronous and Metachronous Lung Metastatic Groups - Gok Durnali, Ayse (PLoS One, 2016)
Osteosarcomas with lung metastases are rather heterogenous group. We aimed to evaluate the clinicopathological characteristics and outcomes of osteosarcoma patients with lung metastases and to compare the synchronous and metachronous lung metastatic groups. A total of 93 adolescent and adult patients with lung metastatic osteosarcoma, from March 1995 to July 2011, in a single center, were included. Sixty-five patients (69.9%) were male. The median age was 19 years (range, 14–74). Thirty-nine patients (41.9%) had synchronous lung metastases (Group A) and 54 patients (58.1%) had metachronous lung metastases (Group B). The 5-year and 10-year post-lung metastases overall survival (PLM-OS) was 17% and 15%, respectively. In multivariate analysis for PLM-OS, time to lung metastases (p = 0.010), number of metastatic pulmonary nodules (p = 0.020), presence of pulmonary metastasectomy (p = 0.007) and presence of chemotherapy for lung metastases (p< 0.001) were found to be independent prognostic factors. The median PLM-OS of Group A and Group B was 16 months and 9 months, respectively. In Group B, the median PLM-OS of the patients who developed lung metastases within 12 months was 6 months, whereas that of the patients who developed lung metastases later was 16 months. Time to lung metastases, number and laterality of metastatic pulmonary nodules, chemotherapy for lung metastatic disease and pulmonary metastasectomy were independent prognostic factors for patients with lung metastatic osteosarcoma. The best PLM-OS was in the subgroup of patients treated both surgery and chemotherapy. The prognosis of the patients who developed lung metastases within 12 months after diagnosis was worst.